The Effect of Macrocyclic Lactones-Ivermectin Exposure on Egg Hatching and Larval Development of Caenorhabditis elegans - Mariani Mohd Zain,; Zary Shariman Yahaya,; Nik Ahmad Irwan Izzauddin Nik Him, (Tropical Life Sciences Research, 2016)
To date, the ivermectin resistance in nematode parasites has been reported and many studies are carried out to determine the causes of this problem. A free-living Caenorhabditis elegans is used as a model system for this study to investigate the response of C. elegans to ivermectin exposure by using larval development assay. Worms were exposed to ivermectin at concentration from 1 ng/mL to 10 ng/mL and dimethyl sulphoxide (DMSO) as a control. The developments of the worms were monitored for 24, 48, 72, and 96 hours until the worms become adults. Results indicated that worms’ growth began to be affected by ivermectin at a concentration of 5 ng/mL, while at the concentration of 6, 7, 8, 9, and 10 ng/mL, the growth of worms were inhibited compared to control worms. Further study of the protein expression in C. elegans should be done to investigate the up-regulated and down-regulated proteins involve in ivermectin resistance.